Post Conflict Development and Status of Implementation of Thirteenth Amendment to the Constitution of Sri Lanka - Sivakumar, S. (The International Journal Research Publications, 2013)
Devolution of power has been an alternative to the demand for separation by the Tamil speaking people in the North, East provinces of Sri Lanka. The Indo-Lanka Accord signed on 29 July 1987 required the Sri Lankan government to devolve powers to the provinces and, in the interim, to merge the Northern and Eastern provinces into one administrative unit. The accord required a referendum to be held by 31 December 1988 in the Eastern Province to decide whether the merger should be permanent. Crucially, the accord allowed the Sri Lankan president to postpone the referendum at his discretion.Unlike any other province, this matter is linked very closely with the political aspirations of the Tamil speaking people. This alternative was accepted by the Tamil speaking people on the guarantee given by the Government of India in late eighties. On 14 November 1987 the Sri Lankan Parliament passed the 13th Amendment to the 1978 Constitution of Sri Lanka and the Provincial Councils Act No 42 of 1987, establishing provincial councils. Nine provincial councils were created by order on 3 February. On September 2 and 8 1988 President Jayewardene issued proclamations enabling the Northern and Eastern provinces to be one administrative unit administered by one elected Council. The North-East Province was born.There are three lists dealing the power sharing mechanism. Author spells out the ways and means of strengthening the power sharing by changing the contents of these three lists based on his research during past couple of years and his experience in the field of development activity.
Keywords: Devolution; Autonomy; North-East Provincial Council